Brief psychological analysis of the film Rosemary’s baby by Roman Polanski (psychopathology and cinema) - Arboccó de los Heros, Manolo (2011)
The following article looks for to analyze one of the classic horror films from the perspective of the psychology and in particular from the psychoanalysis. The relationship between films and psychology is very particular and old, and is on the screen where it is shown many situations of the dark and strange dynamics of human events. The human conduct projects to the outside what minds keep inside and the film projects, very often, our fears, desires and part of what is called the subconscious mind. We will try to give a psychological reading of the related story.